Desorption isotherm model for a Malaysian rough rice variety (MR219) - Ibrahim, Mohd Nordin; Rashti, Kobra Tajaddodi Talab; Spotar, Sergei; Syed Muhammad, Sharifah Kharidah; A. Talib, Rosnita (Universiti Putra Malaysia Press, 2013)
Moisture desorption model of long grain Malaysian rough rice variety (MR219) was experimentally obtained using the static gravimetric method for different combinations of temperature (40, 45, 50, 55°C) and water activities (0.0507 to 0.9331). Five most commonly used models with three parameters namely modified Chung-Pfost, modified GAB, modified Halsey, modified Henderson and modified Oswin and a four parameters model (Zuritz et al., 1978) were determined for their ability to fit the experimental data using non linear regression techniques. Comparisons between all models were made on the basis of standard error of estimate (SEE), residual sum squares (RSS) and residual plots. Based on the results of this study, the Zuritz et al., modified Chung-Pfost and modified GAB models could be useful to predict the desorption EMC of MR219. The modified Halsey, modified Henderson and modified Oswin presented a poor fitting to the experimental data. In addition, the model by Zuritz et al. was found to be the most appropriate equation for representing the desorption isotherm model for MR219 at the range of temperatures from 40°C to 60°C.